The Effect Of Black Sticky Rice Tape Consumption On Alteration Of Saliva Ph On Tsanawiyyah Student Of Islamic Boarding School No.3 Pameungpeuk Sub-District Bandung - Deru Marah Laut (Poltekkes Kemenkes Bandung, 2019)
Background : Saliva in the oral cavity serves not only to help in mastication, but also has a protective function, which is maintaining oral hygiene through cleaning mechanisms and coating any tissue in the oral cavity. Many people now consume fermented foods for dessert dishes such a black sticky rice tape. People know that black sticky rice tape has health benefits, such as for body metabolism and antioxidants. Methods : This research aims to determine the effect of black sticky rice tape consumption on saliva pH on students of Islamic Boarding School No.3 Pameungpeuk, Bandung. The techniques of the research are analytic with quasi experiment design and random sampling tehnique with 45 respondents. The sample is to eat black sticky rice tape as much as 1 tablespoon then do saliva pH examination at 10 minutes after. The saliva pH is measured by digital pH meter analyzed by using T-test dependent. Results : The results of this research indicate that the effect of black sticky rice tape on saliva pH at the time of examination 10 minutes with <0,05 and after tested with the normalization test found p value >0,05. Conclusion : It can be concluded that is a significant effect of the black sticky rice tape on saliva pH on students of Islamic Boarding School No.3 Pameungpeuk, Bandung.